Wages and Gender Composition: Why do Women's Jobs Pay Less? - Macpherson, David A.; Hirsch, Barry T. (Journal of Labor Economics, 1995)
Occupational sex segregation and its relationship with wages during 1973-93 are examined. Wage level and wage change models are estimated using Current Population Survey data matched with measures of occupational skills and job disamenities. Standard analysis confirms that wage levels are substantially lower in predominantly female occupations. Gender composition effects are reduced by about a quarter for women and by over one-half for men following control for skill-related occupational characteristics. Longitudinal analysis indicates that two-thirds or more of the standard gender composition effect is accounted for by occupational characteristics and unmeasured worker skill or taste differences. Copyright 1995 by University of Chicago Press.